Desenvolvimento da teoria spray-flamelet - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This work presents the analysis of a diffusive flame where the trajectory of the reactants flow is represented by the counterflow configuration. This configuration is based in the injection of gaseous and oxidant in opposite directions, establishing a stagnation point between then. In the present model, a determined fraction of the fuel is found in the liquid state in the form of droplets. The mathematical description of the problem is elaborated from the energy and chemical species conservation equation which, after being simplified and described in an auxiliary coordinated system, are integrated along the domain, providing the proprieties of the combustion process. Among the parameters that presents influence over those proprieties, are the spray vaporization parameter, the temperature and fuel fraction in the gas and the position where the fuel in liquid state is injected. The influence of each parameter is studied and discussed in a quantitative and qualitative way, being showed that the fuel fraction in the gas presents great influence over the flame temperature and position.
Keywords: Engenharia mecânica; Chama (Combustão); Mechanical Engineering; Flame (Combustion); spray-flamelet; combustão de spray; spray combustion; sprayflamelet model; CNPQ::ENGENHARIAS